Sunan Gunung Djati Leadership Values to Uphold Indonesian Human Dignity: A Philosophical Approach - Dodo Widarda; Mohamed Ismail (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2022)
This paper aims to describe the relationship between the process of searching for "Indonesian human dignity" and the personality of Sunan Gunung Djati who is an ancestor of this nation. Sunan Gunung Djati is a personal figure in a leadership position that is both profane and sacred at the same time. The method used in writing this paper is a qualitative research method based on the Philosophical Research Method. The model of this study is "Factual Historical Research Regarding Figures" with, (1) Material objects about the leadership values of Sunan Gunung Djati, (2) Formal objects, the values of Sunan Gunung Djati's leadership which are approached philosophically, not through an anthropological approach , sociology, politics, or culture, "but insofar as it provides a vision of human beings according to their essence". This article starts from the question, 1) What is the lineage and spiritual transmission of Sunan Gunung Djati? 2) What are the values of Sunan Gunung Djati's leadership as role models for upholding Indonesian human dignity? From the two questions, answers were obtained and at the same time became the conclusion of this study, 1) From his father's side, he was a descendant of an Egyptian king named Syarif Abdullah with the title Sultan Mahmud, while his mother, Nyai Rara Santang, was also a descendant of "blue blood" because she was the daughter of Prabu Siliwangi, the king of Pajajaran. In addition, based on various text sources, Sunan Gunung Djati experienced spiritual transmission in tariqa knowledge at the center of the spiritual axis of the Islamic world, in Makkah. 2) The values of Sunan Gunung Djati's leadership are reflected in the philosophy: "manuk keduwong dangdang wulung kembang kanigaran" which means that a leader, in the management of people's lives, must be oriented towards improving the quality of life of the weak. In addition, the plus point of Sunan Gunung Djati's leadership, was not only that he was progressively capable of advancing society in the Cirebon Sultanate, he was even a head of government, who doubled as a tariqa murshid at the same time. In terms of the concept of seeking Indonesian human dignity, he is an ideal model of the philosophical conception of al-Insân al-Kâmil which is embodied in the world's concrete history. The recommendation from this paper, we should make Sunan Gunung Djati, as an example of leadership in developing a model of Indonesian human dignity as thought by scholars like Sudjatmoko. More and more studies should be conducted regarding the historical and spiritual role of Sunan Gunung Djati.